(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Teachers should have a deep knowledge of English grammar, because grammar is the basis of the language. In ancient times, all Roman and Latin teachers widely used grammar, and in the 1800s, the grammar-translation method began to be used, which became the basis of English. Grammar involves understanding the linguistic structure that exists in all languages, including languages ​​spoken in all countries, and in addition to knowing how to use words correctly, by learning how these structures work, students can use them to build sentences without having to memorize grammatical rules.